Canones: The Art of Harmony The Canon Tables of the Four Gospels - Bausi, Alessandro; Reudenbach, Bruno; Wimmer, Hanna (Studies in Manuscript Cultures, 2020)
Since early times Christians devised solutions for harmonizing and navigating the Four Gospels, coping with four only partly matching narratives of the Life of Christ. The most sophisticated device were the 'Canon Tables' attributed to Eusebius. Prefaced to the Gospels, the Tables appear since the earliest examples within finely decorated architectural frames, which became a most typical subject of late antique and medieval book art.